2019
DOI: 10.1128/iai.00876-18
|View full text |Cite
|
Sign up to set email alerts
|

The Obligate Intracellular Bacterium Orientia tsutsugamushi Targets NLRC5 To Modulate the Major Histocompatibility Complex Class I Pathway

Abstract: Orientia tsutsugamushiis an obligate intracellular bacterium that infects mononuclear and endothelial cells to cause the emerging global health threat scrub typhus. The ability ofO. tsutsugamushito survive in monocytes facilitates bacterial dissemination to endothelial cells, which can subsequently lead to several potentially fatal sequelae. As a strict intracellular pathogen that lives in the cytoplasm of host cells,O. tsutsugamushihas evolved to counter adaptive immunity. How the pathogen does so and the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…This study showed that the lncRNA XIST (X-inactivation-specific transcript), upregulated in breast cancer cells, promotes cell proliferation, migration and invasion by increasing NLRC5 expression through sponging off miR-125b-5p. An obligate intracellular bacterium Orientia tsutsugamushi , which causes scrub typhus by infecting mononuclear and endothelial cells, was shown to attenuate NLRC5 expression in HeLa cells at the post-transcriptional level [ 203 ]. The blockade of NLRC5 protein expression by O. tsutsugamushi required bacterial protein synthesis and possibly host cell factors as inhibition of NLRC5 protein expression was reversible in a monocytic cell line THP-1 but not in endothelial cells.…”
Section: Regulation Of Nlrc5 Expressionmentioning
confidence: 99%
“…This study showed that the lncRNA XIST (X-inactivation-specific transcript), upregulated in breast cancer cells, promotes cell proliferation, migration and invasion by increasing NLRC5 expression through sponging off miR-125b-5p. An obligate intracellular bacterium Orientia tsutsugamushi , which causes scrub typhus by infecting mononuclear and endothelial cells, was shown to attenuate NLRC5 expression in HeLa cells at the post-transcriptional level [ 203 ]. The blockade of NLRC5 protein expression by O. tsutsugamushi required bacterial protein synthesis and possibly host cell factors as inhibition of NLRC5 protein expression was reversible in a monocytic cell line THP-1 but not in endothelial cells.…”
Section: Regulation Of Nlrc5 Expressionmentioning
confidence: 99%
“…Some may more generally disrupt anterograde protein trafficking and thereby inhibit or slow MHC-1 trafficking to the cell surface [19]. An intracellular bacterium, Orientia tsutsugamushi, may also utilize specific and non-specific means to inhibit MHC-1 delivery to the cell surface [42]. Virulent R. rickettsii displays a dramatic and apparently global down-regulation of anterograde protein trafficking to the plasma membrane.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Nlrc5 knockout mice demonstrate increased bacterial loads of Listeria monocytogenes upon infection 29,33 and reduced viral clearance of influenza A and rotavirus attributed to both reduced basal splenic CD8 + T cells as well as impaired CD8 + T‐cell effector function 34,35 . These observations suggest that targeting the ‘signal transducer and activator of transcription 1–NLRC5–MHC class I’ axis is an attractive strategy for intracellular bacteria to evade host immune responses 36,37 …”
Section: Role Of Nlrc5 In In Vivo Immune Responsesmentioning
confidence: 99%